PERISTIWA CIKINI TAHUN 1957 UPAYA PEMBUNUHAN TERHADAP PRESIDEN SOEKARNO DI JAKARTA - Ishaq, Isjoni Ishaq Isjoni; Saiman, Marwoto Saiman Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The events Cikini is one of the events that occurred in this country, events Cikini is an incident an assassination attempt against the President masterminded by an Islamic movement separatist called GAK (Movement Anti-Communist) formed by Colonel Zulkifli Lubis, former Director of Intelligence Forces Army Vice Chief of Staff. GAK organization itself chaired by the aide Colonel Zulkifli Lubis that Saleh Ibrahim. GAK intent and purpose of this is to hinder the development of communists in Indonesia by violence. Dated 29 September 1955 Indonesian citizens to vote in the first election. In the first general election recorded 43,104,464 people who have the right to vote. Only 37,785,299 are voting 77,987,879 total population of Indonesia in 1954. In other words, only 87.65 percent of voters who exercise their voting rights. The results of this election show the four parties that got a big win, namely the Indonesian National Party (57 seats), Masjumi (57 seats), NU (45 seats) and the Indonesian Communist Party (39 seats), while the other parties only memperleh 1 to 8 seats. Elections I done well, which is a success for Burhanuddin Harahap cabinet, and the cabinet considered Burhanuddin Harahap task has been completed. On February 21, 1957 the President issued a Presidential conception in which he stated that democracy is in use at the time of import is democracy and not in accordance with the personality of the Indonesian nation, therefore he wants to replace with Guided Democracy. The culmination of dissatisfaction over the political wisdom that was delivered by the President Soekarno, occurred on November 30, 1957, at which time it was at the Elementary School Cikini held celebrations lustrum III schools, and the President was present to represent the parents of Megawati and Mohamad Guntur. Genesis is known for its school Cikini Cikini events, namely the treatment of an assassination attempt against the President by throwing grenade by a group of Muslim Youth origin Bima, Sumbawa, West Nusa Tenggara.Keyword: Cikini events, Soekarno, Jakarta